False-positive PET/CT finding of hepatic inflammatory pseudotumor in IgG4-related sclerosing cholangitis - Yildirim, Mustafa; Artas, Hakan; Artas, Gokhan (Elsevier Masson, Corp Off, 2021)
[Abstract Not Available]